ORGANIZATIONAL AND LEGAL ASPECTS FORMATION OF TARO DEVELOPMENT OF CIVIL SERVICE ORGANIZATIONAL CULTURE - Padafet , I. (Theory and Practice of Public Administration, 2020)
The article is devoted to the consideration of organizational and legal support for the formation and development of organizational culture of the civil service in Ukraine on the basis of the analysis of the Strategy for Public Administration Reform of Ukraine until 2021. The structure of organizational culture of the subject of power (according to E. Shane) is developed and its elements are characterized, and also the problem field of implementation of the key measures offered by the legislator is outlined. The organizational culture of the civil service, as well as the national culture in general, is constantly in dynamic motion, going through long phases of its formation, formation and development. This process is influenced by a large number of factors, both external and internal: socio-economic conditions, political situation in the country, communication style, inherent not only in an individual institution but also in the whole sphere, vision of leadership, decision-making and more. It is possible to state the growing importance of organizational culture in the process of reforming the system of public administration. However, the existing approach almost eliminates the pervasive nature of the processes of formation and development of the culture of functioning of the subjects of power relations. It should be emphasized that the existing attempts to study the phenomenon of organizational culture of the civil service are not very representative and not stable methodology of their conduct. To develop the Concept of organizational culture of the civil service, it is advisable to discuss its content with a preliminary more thorough study of the mechanisms of cultivating the basic values of the civil service and its ethical principles. Prospects for further research should be the creation of a system of guiding documents of public policy (Concept-Strategy-Program) for the formation and maintenance of organizational culture in public authorities, as well as the development of scientifically sound methods for organizational culture values monitoring.